2018
DOI: 10.1089/gtmb.2017.0040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms inPRM1,PRM2, andYBX2Genes are Associated with Male Factor Infertility

Abstract: This study demonstrates that the PRM1 c.-190C>A polymorphism is associated with sperm DNA fragmentation, which may impact male infertility in the Turkish population. Further research with larger groups and in various other study populations will be required to clarify the impact of protamine and YBX2 gene polymorphisms on male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Table 1 presentations the features of studies entered to the meta-analysis. The studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published from 2003 to 2019. Twelve studies 23,[26][27][28][29][30][31]33,35,[37][38][39] were reported in Caucasian, four studies 24,32,34,36 in Asian, and one 25 in mixed ethnicities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 presentations the features of studies entered to the meta-analysis. The studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published from 2003 to 2019. Twelve studies 23,[26][27][28][29][30][31]33,35,[37][38][39] were reported in Caucasian, four studies 24,32,34,36 in Asian, and one 25 in mixed ethnicities.…”
Section: Resultsmentioning
confidence: 99%
“…The studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published from 2003 to 2019. Twelve studies 23,[26][27][28][29][30][31]33,35,[37][38][39] were reported in Caucasian, four studies 24,32,34,36 in Asian, and one 25 in mixed ethnicities. The genotyping method was PCR-based in fourteen studies [23][24][25][26][27][28][29][30][31]33,35,[37][38][39] and Mass ARRAY in three studies 32,34,36…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aydos et al () studied the genetic polymorphisms in PRM1, PRM2 and YBX2 genes and their association with male infertility. Their results agreed with the present study as the AA and CA genotypes of the PRM1 c.‐190 C>A polymorphism had a significant association with infertility ( p < 0.001), and the AA genotype was significantly associated with high sperm DNA damage ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%